Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10865-012-9480-7
|View full text |Cite
|
Sign up to set email alerts
|

Videos to influence: a systematic review of effectiveness of video-based education in modifying health behaviors

Abstract: This systematic review examines the effectiveness of videos in modifying health behaviors. We searched PubMed (1975-2012), PsycINFO (1975-2012), EMBASE (1975-2012), and CINAHL (1983-2012) for controlled clinical trials that examined the effectiveness of video interventions in changing health behaviors. Twenty-eight studies comprised of 12,703 subjects were included in the systematic review. Video interventions were variably effective for modifying health behaviors depending on the target behaviors to be influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
199
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(240 citation statements)
references
References 53 publications
13
199
1
8
Order By: Relevance
“…26 Use of educational videos, a potentially cost-effective strategy, is emerging as an effective mode of patient education. 27 Research conducted in Asia has shown that video education can be effective at increasing exclusivity and duration of breastfeeding. Results from a randomized trial conducted in Singapore that investigated the use of a 16-minute breastfeeding video delivered in a clinical setting during the prenatal period, along with counseling by a lactation counselor for 15 minutes and written materials, showed improved rates of exclusive breastfeeding at 6 weeks through 6 months postpartum.…”
mentioning
confidence: 99%
“…26 Use of educational videos, a potentially cost-effective strategy, is emerging as an effective mode of patient education. 27 Research conducted in Asia has shown that video education can be effective at increasing exclusivity and duration of breastfeeding. Results from a randomized trial conducted in Singapore that investigated the use of a 16-minute breastfeeding video delivered in a clinical setting during the prenatal period, along with counseling by a lactation counselor for 15 minutes and written materials, showed improved rates of exclusive breastfeeding at 6 weeks through 6 months postpartum.…”
mentioning
confidence: 99%
“…It can be uniquely helpful in situations where unfolding circumstances may call for different responses, such as precise medical procedures or complex social interactions (54). Role playing such behavior under varying circumstances can help the audience to discern patterns and rules and when to apply them.…”
Section: Prescriptive Scientific Narrativesmentioning
confidence: 99%
“…As a means of delivering educational content, video interventions can be produced with limited resources and thus be cost-effective (Sweat, O'Donnell, & O'Donnell, 2001;Tuong, Larsen, & Armstrong, 2014). If used thoughtfully, video interventions also provide consistent delivery of educational messages in a variety of formats: videotapes, downloaded media files, or streaming videos on Internet websites (Gagliano, 1988).…”
mentioning
confidence: 99%